What the fireflies knew eaudiobook A novel. - Harris, Kai (Penguin Audio, 2022)
An NAACP Image Award Nominee Longlisted for the Center for Fiction's First Novel Prize A Marie Claire Book Club pick Named a Most Anticipated Book of 2022 by * Marie Claire* *Teen Vogue* * Buzzfeed* * Essence * * Ms. Magazine * *NBCNews.com* * Bookriot * * Bookbub* and more!  “Harris rewrites the coming-of-age story with Black girlhood at the center.” — New York Times Book Review In the vein of Jesmyn Ward's Salvage the Bones and Sue Monk Kidd's The Secret Life of Bees , a coming-of-age novel told by almost-eleven-year-old Kenyatta Bernice (KB), as she and her sister try to make sense of their new life with their estranged grandfather in the wake of their father's death and their mother's disappearance   An ode to Black girlhood and adolescence as seen through KB's eyes, What the Fireflies Knew follows KB after her father dies of an overdose and the debts incurred from his addiction cause the loss of the family home in Detroit. Soon thereafter, KB and her teenage sister, Nia, are sent by their overwhelmed mother to live with their estranged grandfather in Lansing, Michigan. Over the course of a single sweltering summer, KB attempts to navigate a world that has turned upside down. Her father has been labeled a fiend. Her mother's smile no longer reaches her eyes. Her sister, once her best friend, now feels like a stranger. Her grandfather is grumpy and silent. The white kids who live across the street are friendly, but only sometimes. And they're all keeping secrets. As KB vacillates between resentment, abandonment, and loneliness, she is forced to carve out a different identity for herself and find her own voice. A dazzling and moving novel about family, identity, and race, What the Fireflies Knew poignantly reveals that heartbreaking but necessary component of growing up—the realization that loved ones can be flawed and that the perfect family we all dream of looks different up close.